2006
DOI: 10.1101/gad1367806
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific RNAi reveals that WT1 expression in nurse cells controls germ cell survival and spermatogenesis

Abstract: Using a novel tissue-specific RNA interference (RNAi) approach that mimics the principle by which naturally occurring microRNAs (miRNA) are made, we demonstrate that the Wilms' tumor 1 (WT1) transcription factor has an essential role in spermatogenesis. Mice depleted of WT1 in Sertoli nurse cells suffered from increased germ cell apoptosis, loss of adherens junctions, disregulation of adherence junction-associated genes, and impaired fertility. These effects were recapitulated in transgenic mice expressing a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 43 publications
8
73
0
2
Order By: Relevance
“…A similar approach has been reported previously for interference with other genes in nurse cells (Rao et al, 2006) and, together with a very recent report (Garbett et al, 2010), our findings show that this technique can be used successfully in the brain. Compared with conditional gene deletion this approach has the advantage that it involves only one mouse line and offers the perspective to be used, in modified forms, in other organisms in which targeted mutagenesis is not feasible.…”
Section: Discussionmentioning
confidence: 58%
“…A similar approach has been reported previously for interference with other genes in nurse cells (Rao et al, 2006) and, together with a very recent report (Garbett et al, 2010), our findings show that this technique can be used successfully in the brain. Compared with conditional gene deletion this approach has the advantage that it involves only one mouse line and offers the perspective to be used, in modified forms, in other organisms in which targeted mutagenesis is not feasible.…”
Section: Discussionmentioning
confidence: 58%
“…For genetic function analysis, multi-gene constructs could be used to investigate combinatorial effects, to determine the presence of functional redundancy, or the degree of synergistic or antagonistic interplay between molecular components (Chung et al, 2006;Rao et al, 2006;Xia et al, 2006). In addition, the ability to co-ordinate transgene expression with gene silencing also renders the technology useful for therapeutic applications which may require the silencing (via intronic siRNA) of a faulty gene or allele followed by substitution with a wild-type or functional gene (via exon transgene expression) (Samakoglu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…RNA expression profiling and follow-up transfection experiments identified several genes misregulated in response to perturbed WT1 in adult Sertoli cells (Rao et al 2006). Among these were Eps8 and Icap1-a, which encode crucial signalling molecules at the apical ES.…”
Section: Dna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%
“…WT1 expression persists in Sertoli cells after gonad formation, but until recently, its functional role in this context was not known, as Wt1-mutant mice die early during embryogenesis. The role of WT1 in Sertoli cells after the bipotential gonad stage was recently addressed by two studies (Gao et al 2006;Rao et al 2006). Gao et al (2006) used a conditional knockout approach to disrupt the Wt1 gene in foetal Sertoli cells at approximately e14.5 and found that this severely disrupted testis cord formation in male embryos and subsequently led to the formation of abnormal tubular architecture and reduced testes size in adult males.…”
Section: Dna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation